Sustainable Development Challenges in Rural Agri‐Economies: A Case of Value‐Added Investment Among Palm Oil Smallholders in Sarawak - Ricky, Kemarau; Daniel Ugih, Echoh; Wee, Hin Boo; Nik Norliati Fitri, Md Nor; Muhammad Ammar, Fakhry Norzin; Zulfaqar, Sa'adi; Zaini, Sakawi; Wan Shafrina, Wan Mohd Jaafar; Oliver, Valentine Eboy; Noorashikin, Md Noor; Stanley, Anak Suab; Muhamad Solehin, Fitry Rosley (John Wiley & Sons, Inc., 2026)
Smallholder participation in value-added processing remains minimal in Malaysia's palm oil sector despite sustained policy commitments to inclusive rural upgrading. This study examines the structural, institutional, and behavioural determinants of smallholders' willingness to pay (WTP) for downstream investment in Sarikei, Sarawak, using a mixed-methods approach combining contingent valuation, logistic regression, and qualitative field evidence from 200 smallholders. The results reveal a pronounced intention–action gap: no respondents were engaged in downstream processing, despite expressed conditional willingness to invest. Econometric analysis shows that WTP is driven primarily by structural endowments—income (OR = 1.57), land ownership security (OR = 1.42), education (OR = 1.35), and land size (OR = 1.28)—while age has no significant effect. Perceived economic and social impacts of value addition are uniformly neutral, reflecting the absence of realised participation. Qualitative evidence attributes this gap to high capital requirements, limited access to finance, weak cooperative institutions, insufficient technical capacity, and lack of local demonstration effects, rather than low awareness or motivation. Overall, the findings reframe smallholder upgrading as an institutional feasibility challenge rather than a preference problem, underscoring the need for sequenced, place-based interventions aligned with SDG 1, SDG 8, SDG 9, and SDG 12.